Prediction Rock Strength Properties for Southern Iraqi Field. Application of Petrophysical and Mechanical Properties Relationship, Using Wireline Log Data - Al-Zubaidy, Worood A.; Al-Jawad, Mohammed S.; Al-Hasnawi, Ali. N. (Journal of Petroleum Research and Studies, 2024)
Rock Strength Properties (Internal Friction Angle